Pengaruh Kepercayaan Diri Terhadap Kemandirian Anak di Taman Kanak-Kanak - rusmayadi - (PEDAGOGIKA, 2020)
This study aims to determine the effect of self-confidence in children's independence in the nursery. This study uses a survey method with a quantitative approach. The survey research in question is describing a causal relationship commonly referred to as path analysis. The samples were randomly determined, namely Lotus Kindergarten, Rahmah Kindergarten, and Kindergarten Aisyiah Perumnas II with a sample of 142 students. Path analysis requires that the data to be analyzed meet several statistical tests, namely: (1) Normality test, (2) Homogeneity Test, (3) Test of Significance and Linearity Test of Regression Coefficient and (4) Multicolourity Test. In this study it was found that there was a significant relationship between Confidence (X1) and Independence (X2). The closeness of the relationship between X1 and X2 is confirmed by the results of testing the hypothesis that there is a positive direct effect of Self-Confidence (X1) on Independence (X2). The results of hypothesis testing indicate that Self Confidence (X1) has a significant effect on Independence (X2) as evidenced by the results of statistical tests. The size of the contribution of the Self Confidence variable to Independence is statistically indicated by the value (ρy1 x ρy1) = 0.32 x 0.32 = 0.10 or 10%. This value indicates that approximately 10% of the variation in the independence of children in kindergarten (Group B) is explained directly by self-confidence.